Comparative study on air gasification of plastic waste and conventional biomass based on coupling of AHP/TOPSIS multi-criteria decision analysis. (January 2022) - Mojaver, Mehran; Hasanzadeh, Rezgar; Azdast, Taher; Park, Chul B.
Abstract: A broad range of conventional biomass and plastic waste types was considered and their air gasification process was modeled using a Gibbs free energy minimization coupled with Lagrange multiplier approach. The comparison between the performances of biomass and plastic waste gasification is the main issue of this study. Another important novelty and contribution of this study is analytical hierarchy process/technique for order performance by similarity to the ideal solution coupled method that is employed in gasification of conventional biomass and plastic waste, to prioritize the considered criteria and to select the best feedstock for gasification. Hydrogen production was linearly reduced in the case of conventional biomass with an in increase in the equivalence ratio; however, there was an optimum equivalence ratio to achieve the highest hydrogen production in plastic waste gasification. Plastic waste had a higher low heating value compared to conventional biomass. However, carbon monoxide and nitrogen production from conventional biomass was smaller than from plastic waste. Ten types of feedstock, comprising six types of conventional biomass and four types of plastic waste, were selected as alternatives. The multi-criteria decision analysis coupled method revealed that waste polypropylene and polyethylene were the best alternatives. Graphical abstract: Image 1 Highlights: Multi-criteria decision analysis was performed on air gasification. Plastic waste and conventional biomass gasifications were compared. Analytical hierarchy process was utilized for criteria weighting. TOPSIS method was hired for alternative ranking. Polypropylene and polyethylene were the best alternatives for air gasification.